الحكم الراشد ومحاربة الفساد – حالة الجزائر - موفق, سهام; رحال, نصر (جامعة الوادي - University of Eloued, 2017)
من خلال هذه الدراسة سنوضح الدور الفعال الذي تلعبه إستراتيجيات وسياسات الحكم الراشد في ضمان تطور المؤسسات ومحاربة الفساد، والتي من خلاله تتحقق عدة غايات على رأسها الوقوف أمام الفقر الذي أصبح يهدد أغلب أفراد المجتمعات، كما لا ننسى مشكلة البطالة التي ظلت هاجسا يعاني منه الكثير من الشباب، وبالتالي كان لزاما على الدول أن تكثف كل الجهود لمواجهة مختلف أشكال الفساد. Through this study we will explain the effective role played by the strategies and policies of good governance in ensuring the development of institutions and fighting corruption, through which several goals are achieved, including standing in front of the poverty that has become a threat to most members of the communities and do not forget the problem of unemployment, which remained obsessed by many young people States had to intensify all efforts to confront various forms of corruption.
مقال
Keywords: الحكم الراشد، الفساد، محاربة أشكال الفساد، مكافحة الفقر، التنمية المستدامة. high governance, corruption, fighting corruption, combating poverty, sustainable development.